Characteristics and Shelf Life of Pedada Fruit Leather (Sonneratia caseolaris) With the Addition of Sorbitol and Kappaphycus alvarezii - Iftitah, Khairaniyatul; Saputra, Eka; Yuli Pujiastuti, Dwi (Universitas Airlangga, 2025)
Fruit leather is a traditional product from Turkey. Kappaphycus alvarezii and sorbitol in making fruit leather are needed to maintain the texture of the product during storage. Sorbitol has a hydrophilic -OH group that is able to bind water (humectant) andK. alvarezii can improve texture and the quality of fruit leather. This study was conducted to determine the effect of sorbitol andK. alvarezii addition on fruit leather characteristics and shelf life of pedada fruit leather products. This study used five treatments and three repetitions. The research parameters include the number of bacterial colonies using the Total Plate Count (TPC) method, nutritional content test, and organoleptic (sensory) test. Data analysis in this study used ANOVA one factor and Duncan's Multiple Range Test (DMRT) for quantitative data and Kruskal-Wallis test for qualitative data. The results showed that the samples with the number of bacterial colonies that met SNI 7388-2009 standards were only samples before treatment, 1 week, 2 weeks and 3 weeks of storage. The moisture content of each treatment met the standard of <25%. The results of panelist assessment showed that the shelf life of fruit leather products did not significantly affect (p>0.05) the organoleptic test aspects tested such as appearance, aroma, taste, and texture.